High Sensitivity CReactive Protein (hsCRP) Level on Premature Rupture of Membrane (PROM) at Term Pregnancy - Manoppo, Meily; Tendean, Hermie MM; Sondakh, Joice MM (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To compare the level of high sensitivity C-Reactive Protein (hs-CRP) on patients with premature rupture of membranes (PROM) at term pregnancy. Methods: The study was cross-sectional design. The data collection included age, parity, gestational age, birth weight, and APGAR score on 28 pregnant women at term pregnancy consisting of 14 subjects of Premature Rupture of Membrane (PROM) less than 12 hours and the remaining one was equal or more than 12 hours. We took blood samples from the subjects for the examination of hs-CRP level. Data were analyzed using non-parametric statistical test and processed using Statistical Package for Social Sciences (SPSS) version 20. Results: The mean hs-CRP level on PROM <12-hour and 12-hour group was 12.9 and 17.8 mg/l. There was not significant difference on hs-CRP level between both of group at term pregnancy (p=0.734). Conclusion: The level of hs-CRP does not have association with the incidence of PROM. [Indones J Obstet Gynecol 2017; 5-1: 12-15] Keywords: high sensitivity C-Reactive Protein, premature ruptures of membranes, term pregnancy